Role of a Wastewater Treatment Plant in the Dissemination and Control of Antimicrobial Resistance in Wastewater and Receiving Water - Vanesa Benito; Naroa Lopez-Herguedas; Maite Cabañas; Santos Paunero; Ane Rivas-Macho; Iker Alvarez-Mora; Manu Soto; Felipe Goñi-de-Cerio (Environments, 2026)
Wastewater treatment plants (WWTPs) are key nodes in the environmental dissemination of antimicrobial resistance (AMR), although their net role as sources or barriers of antibiotic-resistant bacteria (ARB) and antibiotic resistance genes (ARG) under full-scale conditions remains insufficiently understood. This study evaluated the occurrence and dynamics of ARB and ARG in a full-scale urban WWTP and its receiving river over a two-year monitoring campaign. Samples were collected from the WWTP influent and effluent, and from river water upstream and downstream of the discharge point, enabling an integrated assessment of treatment performance and potential environmental dissemination. Wastewater treatment markedly reduced AMR indicators, with ARG concentrations decreasing by at least 90% from influent to effluent. No consistent increase in ARB or ARG levels was observed downstream compared with upstream, indicating no measurable dissemination attributable to the WWTP discharge. Multidrug-resistant bacteria were prevalent across all compartments, highlighting widespread background resistance in the urban water cycle. Temporal analysis revealed higher ARG abundances in 2021 and 2022 than 2020, consistent with possible changes in antibiotic consumption during the COVID-19 pandemic. Overall, the investigated WWTP did not act as a net AMR source, highlighting its potential role as a control point and the value of integrated monitoring for assessing AMR dynamics and environmental risk.